Pertumbuhan Kredit Sebagai Variabel Mediasi Faktor Yang Memengaruhi Pertumbuhan Laba - Wahyu Rian Hidayat; Hedwigis Esti Riwayati (Sekolah Pascasarjana Perbanas Jakarta, 2017)
This study aimed to analyze the credit growth as mediating influence of capital in the value of the Capital Adequacy Ratio, profitability in the value of the Return On Assets and Return On Equity as well as efficiency in the value of the Operating Expenses and Operating Income to earning growth. Data were analyzed using Partial Least Square. Based on the results of hypothesis testing shows that capital had no significant effect on earning growth. Profitability significant positive effect on earning growth. Efficiency no significant effect on earning growth. capital significant negative effect on credit growth. profitability significant positive effect on credit growth. efficiency significant positive effect on credit growth. Credit Growth variable is unable to mediate capital, profitability and efficiency on earning growth. Attested by insignificant indirect effect.